POST-COVID SYNDROME: PREVALENCE, COURSE FORMS, DIAGNOSTIC ASPECTS - Rakhimov Shermat Ismatovich (Galaxy International Interdisciplinary Research Journal, 2023)
Post-COVID syndrome also known as long COVID refers to symptoms persisting for more than three weeks after the diagnosis of COVID-19. We reviewed the current evidence on post-COVID syndrome, focusing on its clinical manifestations and addressing the challenges for its management in primary healthcare. The incidence of post-COVID syndrome is estimated at 10–35%, while for hospitalized patients it may reach 85%. Fatigue is the most common symptom reported in 17.5–72% of post-COVID cases, followed by residual dyspnea with an incidence ranging from 10–40%. Mental problems, chest pain, and olfactory and gustatory dysfunction may affect up to 26, 22 and 11% of patients, respectively. More than one third of patients with post-COVID syndrome have pre-existing comorbidities, hypertension and diabetes mellitus being the most common. Beyond the prolonged duration of symptoms, the scarce published data indicate that most patients with post-COVID syndrome have a good prognosis with no further complications or fatal outcomes reported. Given the clinical spectrum of patients with post-COVID syndrome, most of them will be managed by primary healthcare professionals, in conjunction with pre-existing or new co-morbidities, which, in turn, may increase the burden of COVID-19 on primary healthcare. In conclusion approximately 10% of patients with COVID-19 may have symptoms persisting beyond three weeks, fulfilling the criteria of post-COVID syndrome. Primary healthcare professionals have a key role in the management of patients with post-COVID syndrome. Research is needed to elucidate the pathogenesis, clinical spectrum, and prognosis of post-COVID syndrome.